Human Rights in Indonesia - Juwana, Hikmahanto (Indonesian Journal of International Law, 2021)
Indonesia is the parties of international convention on human rights. Indonesia has raised the problems of human rights from its constitution, even the problem is not the main concern. Another aspect which has the important role to the protection of human rights besides the substantive law is the institution, either it is a government institution or non government institution, whose dealing with the human rights problem. The National Commission on human rights (KOMNASHAM) is the first government institution whose established for handling the problems of human rights.